Design of DC-DC buck-boost non-inverting converter using pic microcontroller - Ahmed Khudhair Abbas (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2015)
The main aim of this research is the input voltage, which comes from a varaible sources. It is required to control model of buck-boost non-inverting converter controller by a duty cycle of PWM signal.